Numerical simulation of wellbore temperature effects on pipe column crystallization during hydrogen storage and brine discharge in salt caverns - Liu, Wei; Ma, Rui; Li, Qihang; Wang, Yifan; Cen, Xueqi; Wu, Lang (International journal of hydrogen energy, 2025)
Against the backdrop of achieving the dual carbon goals, salt cavern hydrogen storage (SCHS) has emerged as a pivotal technology for supporting renewable energy consumption due to its large-scale storage capacity, low energy attenuation, and cross-seasonal regulation capabilities. However, during the construction of salt caverns, the issue of salt crystallization caused by the coupling of wellbore temperature gradients and flow velocity fluctuations poses a significant threat to hydrogen pipeline transportation efficiency. In this research, a transient model was developed based on fluid-solid heat transfer theory to investigate the effects of injection and discharge parameters, as well as salt cavern construction approaches, on wellbore temperature and crystallization behavior. Furthermore, a multi-parameter coupled prediction model was established using the response surface methodology. Herein the results indicate that for every 200 m increase in salt cavern burial depth, the crystallization risk increases by a factor of 2.3, while the temperature rises by 17.95 °C (at a burial depth of 1800 m). For every 10 m3/h increase in flow rate, the crystallization position shifts upward by 12.9 m. The brine cooling amplitude in two-butted-well horizontal cavern construction (6.82 °C) is lower than that in single-well vertical construction (11.92 °C); nevertheless, the extended migration path intensifies local supersaturation. Response surface analysis reveals that the interaction between geothermal gradients and freshwater temperature exerts the most substantial influence. Hence, the findings of this study can provides theoretical support for the anti-blocking design and operation and maintenance optimization of brine pipelines in SCHS projects.